Addressing the research gap: access to care hinders genetic discovery in systemic lupus erythematosus patients throughout the African diaspora - Hwang, Jihwan; Dzifa Dey, Ida; Ayanlowo, Olusola; Flower, Cindy; King, Amanda; Johnson, Nicole; Ima-Edomwonyi, Uyiekpen; Olasebikan, Hakeem; Falasinnu, Titilola; Durairaj Pandian, Vishnuprabu; Blazer, Ashira (Frontiers in Genetics, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune condition that disproportionately impacts non-White ethnic and racial groups, particularly individuals in the African diaspora who experience heightened incidence, prevalence, and adverse outcomes. Genetic and epigenetic factors play significant roles in SLE risk, however these factors neither explain the whole of SLE risk nor the stark racial disparities we observe. Moreover, our understanding of genetic risk factors within African ancestry populations is limited due to social and environmental influences on research participation, disease presentation, and healthcare access. Globally, the African diaspora faces barriers in accessing essential SLE diagnostic tools, therapeutics, healthcare practitioners, and high-quality clinical and translational research studies. Here, we provide insights into the current state of genetic studies within African ancestry populations and highlight the unique challenges encountered in SLE care and research across countries of varying income levels. We also identify opportunities to address these disparities and promote scientific equity for individuals affected by SLE within the global African diaspora.